Blockchain Technology—a Breakthrough Innovation for Modern Industries (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Reprint, titled "Blockchain Technology—A Breakthrough Innovation for Modern Industries", provides an insightful exploration of how blockchain is revolutionizing industries by enhancing transparency, security, and efficiency. This collection comprises cutting-edge research and comprehensive reviews that address the challenges and opportunities blockchain presents across diverse sectors. The articles delve into theoretical advancements, innovative methodologies, and real-world applications of blockchain technology. Key themes include enhancing supply chain traceability, integrating blockchain with other advanced technologies like IoT and AI, securing financial transactions, and addressing cybersecurity threats in critical infrastructures. These contributions demonstrate blockchain's potential to drive sustainable development and foster innovation while tackling pressing industry challenges, such as scalability, interoperability, and regulatory compliance. Curated by guest editors involved in the W.E. B.E.S.T. (blockchain and smart contracts for the enhancement of the made in Italy excellence supply chains) project, this Reprint bridges academic research with practical insights, offering value to researchers, industry professionals, and policymakers alike.